Adaptive Learning Based on Artificial Intelligence Technology in Improving the Quality of Graduates (Case Study of SDN 4 Ciseureuh Students in the Context of Digitalization) - Suharyanto H. Soro; Nana Herdiana Abdul Rahman; Wita Puspita Sari; Elis Nursari (Global Education Journal, 2026)
Artificial Intelligence technology is implemented through a learning platform that is able to automatically adjust the material based on individual student performance and interests. However, in the realities at school, there are still many students who have difficulty in utilizing this technology. The purpose of this study is to analyze the application of adaptive learning integrating artificial intelligence (AI) technology and its impact on improving the quality of graduates. The research method used is a descriptive qualitative method with a case study approach. Data was collected through participatory observation, in-depth interviews, and documentation. The results of the study show that (1) the integration of AI in adaptive learning can significantly improve the quality of graduates because the material is presented according to the level of understanding; (2) Teachers' time efficiency in assessing and mapping student competencies. This study concludes that AI technology as an instrument is used in learning activities so that it can improve the quality of graduates.